ANALISIS FRASA VERBA PADA TEKS BERITA BBC.COM BERJUDUL â€œPILKADA 2020 DI TENGAH PANDEMI COVID-19: MASA KAMPANYE DIMULAI, CARA TATAP MUKA TETAP DINILAI PALING EFEKTIFâ€ - Dyah Ayu Widyawati C.P.; Asep Purwo Yudi Utomo (CARAKA, 2020)
Phrases are often found in text in a sentence, which is in the bbc.com news text entitled "Pilkada 2020 in the Middle of the Covid-19 Pandemic: The Campaign Period begins, Face-to-Face Remaining is considered the Most Effective" The research objective was to analyze verb phrases, namely verb phrases modified, coordinative, and apologetic. The research method uses descriptive qualitative methods, with reading, note-taking, and substitution techniques, then the analysis of the research data this time uses the split method. From the research results obtained data of 11 verb phrases. With the results of this verb phrase analysis, more detailed research on verb phrase analysis can be carried out.